Green/red pulsed vortex-beam oscillations in all-fiber lasers with visible-resonance gold nanorods. Issue 34 (19th August 2019) - Zou, Jinhai; Kang, Zhe; Wang, Rui; Wang, Hongjian; Liu, Jiaxing; Dong, Chuchu; Jiang, Xiantao; Xu, Bin; Cai, Zhiping; Qin, Guanshi; Zhang, Han; Luo, Zhengqian
Abstract : We demonstrate visible-wavelength all-fiber pulsed vortex lasers for the first time that may serve as attractive alternatives to solid-state vortex lasers for a variety of applications, such as visible mode-division multiplexing and STED microscopy. Abstract : Optical vortex beams are of tremendous interest in diverse applications for optical tweezers, high-resolution imaging, quantum information and optical communications. So far, these vortex laser sources largely rely on extra-cavity mode conversion by bulk optical elements ( e.g. spatial light modulators, phase plates, etc. ), resulting in a relatively poor purity, low conversion efficiency, non-compact structure and expensive package. Vortex beams generated directly from cavity-mode lasers is naturally an ideal solution, but almost all of them are not extended into the important visible spectral region. Here, we address the challenge through demonstrating, for the first time, visible-wavelength all-fiber pulsed vortex lasers. By using the fiber offset splicing technique and all-fiber visible resonators, 543.6 nm (green) and 634.7 nm (red) vortex beams are generated directly from Er 3+ : ZBLAN and Pr 3+ /Yb 3+ : ZBLAN fiber lasers with topological charges of ±1 and ±2, respectively. In particular, by exploiting an excellent visible-wavelength saturable absorber, visible-resonance-controlled gold nanorods, we further realize stable short-pulse operation of the 543.6 nm/634.7 nm vortex beams in the miniaturized visible fiber lasers. The green/red vortex laser pulses are ∼500 ns in duration, have a 40–400 kHz tunable repetition rate, and a >45 dB RF signal-to-noise ratio. This work may pave a path towards compact visible-wavelength pulsed vortex lasers for specific applications in STED microscopy and visible-light communications.